Chemical-genetic inhibition of a sensitized mutant myosin Vb demonstrates a role in peripheral-pericentriolar membrane traffic - Provance, D. William (National Academy of Sciences, 2004)
Selective, in situ inhibition of individual unconventional myosins is a powerful approach to determine their specific physiological functions. Here, we report the engineering of a myosin Vb mutant that still hydrolyzes ATP, yet is selectively sensitized to an N(6)-substituted ADP analog that inhibits its activity, causing it to remain tightly bound to actin. Inhibition of the sensitized mutant causes inhibition of accumulation of transferrin in the cytoplasm and increases levels of plasma-membrane transferrin receptor, suggesting that myosin Vb functions in traffic between peripheral and pericentrosomal compartments.